Building students' Background knowledge on Reading Comprehension through PreP Method for the Tenth Grade Students at SMA Negeri 1 Tiakur - Souisa, Threesje Roza; Meyer, Fredy (Koli Journal : English Language Education, 2020)
Building students' background knowledge is an integral part in reading instruction; hence it should be done with applicable teaching method and Prep is recommended method that effective for EFL students. This study attempts to help students build their prior knowledge as well as their reading comprehension by using Prep method and find out the strengths and weakness of this method in EFL reading activities.This study employed a classroom action research as a research design to treat students through Prep method in teaching reading comprehension. It took place in State SMA 1 Tiakur, particularly for the tenth grade students consisted of 22 students as the subject of the study. To gain comprehensive data, this study utilized an observation checklist, the field notes, questionnaire, test and quizzes as data instruments. The data were analyzed both descriptively quantitatively and qualitatively ways. The result of this study shows that The PreP Method is affected in building the students’ prior knowledge as the bridge to explore deeply the new materials, improve the students’ vocabularies and reading comprehension, encourage the students to actively involve and enjoy fell happy or feel attracted, motivated and challenged to explore reading texts